Spectra of algebras of symmetric and subsymmetric analytic functions - Zagorodnyuk, A.V.; Chernega, I.V. (Carpathian Mathematical Publications, 2010)
Algebras of symmetric and subsymmetric analytic functions of bounded type on spaces L_1[0,∞)L_∞[0,∞) and L_∞[0,1] and their spectra are investigated.